2014
DOI: 10.1016/j.repc.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Serum visfatin and omentin levels in slow coronary flow

Abstract: Adipocytokines such as visfatin and omentin may play a role in the pathogenesis of coronary slow flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The difference between the two groups was signi cant (P = 0.003). Studies have shown that reducing the level of omentin-1 in serum leads to slow coronary blood ow, and, except for acute coronary syndrome, the level of plasma omentin-1 in patients with stable coronary heart disease is lower than that in normal controls [22,7]. Serum omentin-1 levels have been shown to decrease at the onset of acute coronary syndrome and then increase after 6 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the two groups was signi cant (P = 0.003). Studies have shown that reducing the level of omentin-1 in serum leads to slow coronary blood ow, and, except for acute coronary syndrome, the level of plasma omentin-1 in patients with stable coronary heart disease is lower than that in normal controls [22,7]. Serum omentin-1 levels have been shown to decrease at the onset of acute coronary syndrome and then increase after 6 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that myocardial fibrosis promotes various conduction abnormalities and causes malignant VA to occur [ 29 32 ]. Furthermore, considering its key role in unstable plaques, higher circulating visfatin concentrations have been observed in patients with slow coronary flow [ 33 ], which contributes to malignant VA. Notably, visfatin levels also differed statistically between patients with benign VA and control patients without SHD.…”
Section: Discussionmentioning
confidence: 99%
“…26 Studies detected an association between inflammatory markers and the SYNTAX score, and found a strong correlation between these markers and the extent of CAD. 7,27 The role of visfatin in the inflammatory process and in the maturation of vascular smooth muscle cells 28 can shed light on a possible effect of coronary atherosclerosis. Therefore, visfatin may act as a proinflammatory cytokine, play a role in chronic inflammation, and may contribute to the pathogenesis of atherosclerosis and CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Visfatin may be related to endothelial function, which is indispensable for coronary circulation, and may be an indicator of an inflammatory event in the coronary arteries. 7 Many studies have investigated the relationship between inflammation markers and the extent of CAD. 810 In this study, we emphasized that inflammation involved with the severity and extent of coronary atherosclerosis might be related to serum visfatin level in patients with stable CAD.…”
Section: Introductionmentioning
confidence: 99%